Implementation of Peer-To-Peer (P2p) Computer Networks in Digital Content Distribution Systems to Increase Accessibility and Efficiency - Pohan, Muhammad Taslim; Badawi, Afif (Bahasa Indonesia, 2023)
In the ever-growing digital era, digital content distribution has become very important in various fields, such as media, entertainment and education. The implementation of peer-topeer (P2P) computer networks has become an effective solution in increasing accessibility and efficiency in the distribution of digital content. The implementation of P2P computer networks allows digital content to be distributed in a decentralized manner, where each user acts as a host and client simultaneously. This eliminates dependency on a central server and allows content to be distributed more efficiently and quickly. In addition, with the P2P system, accessibility to digital content can be increased, especially in areas that have limited internet access. The advantage of implementing P2P computer networks in digital content distribution systems is increased accessibility. In a P2P system, content can be distributed more quickly and efficiently because there is no bottleneck at one central point. Instead, content can be distributed from multiple sources simultaneously, optimizing the use of available network capacity. This means users can download or access content at high speeds and with lower waiting times. In implementing a P2P computer network, it is necessary to consider security and network management aspects. Protection of copyright, integrity and authenticity of content is important in this system. In addition, network resources and traffic management must be managed well to maintain network quality.